EVALUATION OF MORPHO-PHYSIOLOGICAL RESPONSES OF WHEAT GENOTYPES AGAINST DROUGHT STRESS IN PRESENCE OF A LEONARDITE DERIVED HUMIC FERTILIZER UNDER GREENHOUSE CONDITION - Y. Peymaninia; M. Valizadeh; R. Shahryari; M. Ahmadizadeh (Journal of Animal and Plant Sciences, 2012)
The present study was carried out for evaluation response of 12 bread wheat genotypes to a liquid humic fertilizer based on Leonardite against terminal drought stress. Analysis of variance of data showed that there was considerable variability among genotypes in all of the studied traits except of maximum total fluorescence value (Fm), which demonstrate the presence of genetic diversity among wheat genotypes. Irrigation mean squares were also significant for all the studied traits except of Fv/Fm, total tillers, fertile tillers, plant height and spike length showing that the water stress has significant effect on traits. Irrigation and Leonardite interaction was significant for Fv/Fm, Fm, fertile tillers and plant height, non-significant irrigation and leonardite interaction for another traits it could be indicated that used potassium humate in this study has no effect on these traits in normal and drought stress conditions. As result, it concluded that in our experimental conditions, grain yield of wheat genotypes was reduced under drought stress condition. But fluorescence parameter increased in drought stress condition and humic fertilizer didn’t affect genotypes. Genotype MV17/zrn produced the highest biological yield, spike weight, spike length, number of grain per spike and grain yield. Therefore, Genotype MV17/zrn performed better than others.
Keywords: Bread wheat; Potassium humate; Drought stress; Chlorophyll fluorescence.